214k views
16 votes
2.) 3(10x + 9) - 9(3x - 5)


SHOW WORK PLEASE

User Cobrexus
by
4.7k points

2 Answers

1 vote

Answer:

Let's simplify step-by-step.

3(10x+9)−9(3x−5)

Distribute:

=(3)(10x)+(3)(9)+(−9)(3x)+(−9)(−5)

=30x+27+−27x+45

Combine Like Terms:

=30x+27+−27x+45

=(30x+−27x)+(27+45)

=3x+72

User Sourabh Bhardwaj
by
4.5k points
6 votes

Answer:

3x+72

Explanation:

Let's first simplify the equation 3(10x+9)−9(3x−5)

You want to distribute first

=(3)(10x)+(3)(9)+(−9)(3x)+(−9)(−5)

=30x+27+−27x+45

And then combine like terms:

=30x+27+−27x+45

=(30x+−27x)+(27+45)

=3x+72 (answer)

User Kamala
by
5.5k points